THE PREDICTION OF BANKRUPTCY WITH MODEL GROVER, ALTMAN Z-SCORE, AND ZAVGREN LOGIT IN COMPANY RETAIL RELEASE REGISTERED IN BEI " (2014-2016) - Anis Nindriyani; Rina Ani Sapariyah; Septiana Novita Dewi (ADVANCE, 2018)
This research aims to provide empirical evidence that: there is a difference between the model of Grover Altman Z-Score, and Zavgren Logit on Retail Company. The sample used in this research is Retail Company listed in BEI 2014-2016 by using purposive sampling method. The types and sources of data used are secondary data in the form of financial reports published and downloaded from the official website IDX. the analytical techniques used to measure the potential for bankruptcy are Grover, Altman Z-Score, and Zavgren Logit models. The determination of the differences between the models is One Way Anova Kruskal-Wallis Test and Mann Whitney  U Test . The result of the research with Grover model shows 1 company entering bankrupt category and 16 companies entering category not bankrupt. Altman Z-Score model shows 1 company entering the category of bankruptcy, 9 companies enter the category of vulnerable and 7 companies enter the healthy category. Zavgren Logit model shows 6 companies enter the category of vulnerable and 11 companies enter the healthy category. One Way Anova Kruskal-Wallis test results  a significant difference from the three models in predicting of bankruptcy Retail companies. Man Whitney U Test test results show there is no significant difference in the Grover-Zavgren Logit model and there are significant differences between the Altman Z-Score - Zavgren Logit models and Grover - Altman Z-Score.Keywords: Bankruptcy, Grover, Altman Z-Score, Zavgren Logit